The Evaluation Between The Impact Of Using Isoflurane And Propofol On Shivering Among Patients Undergoing Vitrectomy Surgery - Maryam Kheirandish; Fariborz Mehrani; Kosar Kian; Saeed Vahedi (Tehran University of Medical Sciences, 2016)
Background and Aim: The postoperative shivering is one of the common complications of anesthesia, which can cause increased systemic blood pressure, oxygen consumption, intra optical pressure and heart rate in patients. It is necessary to   choose an effective intravenous and the inhaled drugs to reduce postoperative shivering, therefore the aim of this study was to compare Isoflurane and Propofol on shivering among patients undergoing Vitrectomy Surgery. Materials and Methods: In a double-blind clinical trial, 112 patients aged 16 to 75 (ASA class I-III) who underwent the Vitrectomy surgery were randomly classified into two groups of 56 cases. The occurrence of postoperative shivering in recovery were registered in both groups. Findings were analyzed employing the t-test and Chi-square. Statistical significance was accepted for P values of <0.05. Results: There was no significant difference between the two groups in terms of age, sex, Weigh، duration of  surgery and duration of anesthesia. The incidence of shivering in recipients of Isoflurane and in recipients of propofol was 12.5% and 32.1% respectively. Conclusion: Using Isoflurane is better than Propofol to reduce the postoperative shivering in patients undergoing the vitrectomy surgery.